EFFECT OF BORDER CROPS ON POPULATION BUILDUP OF WHITEFLY, APHIDS AND VIRUS INCIDENCE IN POTATO CROP - Bhatanagar, Anuj (Potato Journal, 2019)
Potato J (2018) 45 (2): 99-106EFFECT OF BORDER CROPS ON POPULATIONBUILDUP OF WHITEFLY, APHIDS AND VIRUSINCIDENCE IN POTATO CROPAnuj Bhatnagar1, RP Pant2 and SK Chakrabarti3ABSTRACT: Field experiments were conducted over two years to determine the effect of maize and mustard as border crops on buildup of whitefly and aphid populations and transmitted virus diseases in potato during 20113-14 and 2014-15 at Modipuram, India. The results indicated that placement of mustard as trap crop towards south direction in potato plots reduced aphid and whitefly population and also reduced virus incidence to a level of 1.3 per cent followed bymustard placed on north direction (1.2%) in comparison to control (4.7 and 6.4%) . However, the maize as border crop had comparatively less significant effect on the buildup of vector population and corresponding diseases development in potato crop as compared to mustard crop. The result indicated that mustard border rose at south and north directions in potato field would be effective in the management of potato aphids, whitefly and corresponding transmitted virus diseases in comparison to maize border. The significant effect of the mustard border on tuber yield shows that the technology wouldbe most ideal for small scale potato production that could be done in small propagation plots planted with mustard as trap crop toward south and north directions.